2005
DOI: 10.1111/j.1468-3148.2005.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Obesity among Children and Adolescents with Intellectual Disabilities in Taiwan

Abstract: Background Obesity and the health problems associated with it have substantial economic consequences for health care systems. Little information is available concerning obesity-related problems among people with intellectual disabilities. The aims of this study were to analyse patterns of obesity among children and adolescents with intellectual disabilities in Taiwan and to compare these data with existing national norms in an attempt to identify the scale of the problem of obesity among this population. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
2
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 34 publications
(43 reference statements)
8
58
2
3
Order By: Relevance
“…Parmi ces troubles, le développement du surpoids et de l'obésité est tout particulièrement prégnant. En effet, de récentes études rapportent, chez les adolescents DI, des niveaux de prévalence de surpoids et (ou) d'obésité systématiquement supérieurs à ceux observés chez les adolescents sans DI, et cela quel que soit le contexte d'accompagnement [23][24][25][26][27] . L'apparition de cette pathologie secondaire est particulièrement préoccupante, car elle risque de devenir sur-handicapante sur le plan physique 28,29 et psychosocial 30 .…”
Section: Limitationsunclassified
“…Parmi ces troubles, le développement du surpoids et de l'obésité est tout particulièrement prégnant. En effet, de récentes études rapportent, chez les adolescents DI, des niveaux de prévalence de surpoids et (ou) d'obésité systématiquement supérieurs à ceux observés chez les adolescents sans DI, et cela quel que soit le contexte d'accompagnement [23][24][25][26][27] . L'apparition de cette pathologie secondaire est particulièrement préoccupante, car elle risque de devenir sur-handicapante sur le plan physique 28,29 et psychosocial 30 .…”
Section: Limitationsunclassified
“…To our understanding, considerable attention had been given to the younger population as this disability originates before the age of 18. Researchers from around the world have reported that the prevalence of obesity in children with intellectual disability varies from 3% to 37% (Begarie, Maiano, Leconte, & Ninot, 2013;Lin, Yen, Li, & Wu, 2005;Mikulovic et al, 2011;Rimmer, Yamaki, Davis, Wang, & Vogel, 2011;Stewart et al, 2009) and that the prevalence is at least as high if not higher than their typically developing peers (Bandini, Curtin, Hamad, Tybor, & Must, 2005;Chen, Kim, Houtrow, & Newacheck, 2009;Curtin, Anderson, Must, & Bandini, 2010;Must et al, 2014). With the population of individuals with intellectual disability ageing; there is a dire need to study the adult population.…”
Section: Methodsmentioning
confidence: 99%
“…A higher prevalence of obesity has been reported among non-representative samples of youth with spina bifida (5) , cerebral palsy (6,7) , Down's syndrome (8) and intellectual disability (9)(10)(11)(12) . Obesity among youth with I/DD may undermine their ability to live independently, limit future opportunities for employment, and may contribute to health disparities in adulthood (13) .…”
mentioning
confidence: 99%